A Qualitative Study: Availability of Health Facilities as Part of Supporting the Implementation of the Health Referral System - Sartini Risky; Alida Palilati; Muhammad Amir; Nani Yuniar (Institute of Medico-legal Publications Pvt Ltd, 2021)
The referral problem in Southeast Sulawesi is still quite complex. Based on preliminary studies conductedat several health centers, it was found that there were several problems related to human resources, time,facilities and infrastructure. The basic thing that was found was lack of availability of facilities and infrastructure. The results of observations at several Public Health Care found that several other complaintsrelated to the BPJS (Social Security Administrator) referral system that were felt were the lack of facilities inprimary health services and some damaged facilities so that cases that should have been handled at primary/ secondary services were immediately referred to tertiary hospitals. This research is a qualitative research,The research was conducted at the Public Health Care of Kendari City and Bau-Bau City from February2020 to completion. aspects of facilities and infrastructure as an important aspect in the implementationof The referral system is still inadequate in terms of the quantity of facilities and infrastructure as well ascompliance with the compendium. The referral system is still inadequate in terms of both the number ofdrugs and the suitability of the formulary.